Analyse des contraintes foncières et culturales du maraichage dans le département de Kantché au Niger: cas du périmètre irrigué de Tassaou - Illou Mahamadou; Bonkoungou Joachim; Souley Kabirou; Oumarou Bagoudou Sani (European Scientific Journal, ESJ, 2018)
Irrigated crops are a credible alternative when it comes to freeing agricultural production from rainfall hazards. In addition to the irregularity and poor distribution of rainfall, the department of Kantché suffers from enormous problems related to the environment, socio-economic and sociodemographic contexts. This work proposes to analyse land and cultural constraints in order to promote the local economy. The objective is to diagnose the question of distribution and access to land. It is also a critical examination of the evolution of crops and the main constraints. To achieve this objective, the methodological approach was based on socio-economic surveys that collected quantitative and qualitative data. The main results show that there are disparities in land availability among farmers. Inheritance remains the main mode of access to land, but the purchase is becoming more and more important. With regard to crops, environmental and socio-economic conditions have led producers to abandon some crops in favor of others. The major difficulties are the poor distribution and irregularity of rains, the drop in soil fertility, parasitic attacks and cultivation techniques.